Tetra-Carbazole based electroactive donor-acceptor dyes: Effect of the phenyl bridging unit on the electrochromic performance - Doyranli, Ceylan; Altinisik, Sinem; Ozdemir, Mucahit; Koyuncu, Sermet (ELSEVIER SCI LTD, 2022)
In this study, a new Donor-Acceptor-Donor (D-A-D) electroactive molecules (HCQM1 and HCQM2) containing 9H-carbazole and 9-phenyl-9H-carbazole as donor along with quinoxaline (HQ) as acceptor were synthesized and then coated on Indium Tin Oxide/Glass (ITO/Glass) surface by the electrochemical oxidation process. The HOMO-LUMO band gap values obtained by electrochemical oxidation and reduction onsets were calculated as 2.64 and 2.68 eV, respectively. On the other hand, UV-Vis absorption measurements showed that the charge transfer band of HCQM1 was detected at 500 nm with 50 nm red shift upon compared with the HCQM2. According to AFM results, it is seen that the roughness of the poly(HCQM2) film is higher than the poly(HCQM1) film. Finally, the polymer film of HCQM2 showed multi-electrochromic color change (yellow, green, and dark blue) upon the oxidation process. When the electrochromic performance of the HCQM1 and HCQM2 polymer films was compared, it was discovered that the HCQM2 with phenylene spacer unit has better stability and a higher percentage transmittance change (& UDelta;T%) between neutral and oxidized states.
Keywords: Donor-acceptor dyes; Carbazole; Quinoxaline; Electrochromic materials; FLUORESCENT SENSOR; ENERGY-STORAGE; BAND-GAP; POLYMERS; DEVICE; Chemistry; Engineering; Materials Science